The Contribution of English Clubs to the Teaching and Learning of EFL with Post-Beginners at Lycée Toffa 1er, Porto-Novo - LOKO, Djima Crépin; YESSOUFOU, AKIMI (My University, 2023)
This research intends to show the contribution of English club activities to communicative English learning in a French-speaking context like Benin. The study proceeds by a test/control research approach, combining both quantitative and qualitative methods. Data have thus been collected using two tests, interview and direct observation with a sample of 20 participants of whom 16 students in the fourth form, four EFL teachers from Lycée Toffa 1er de Jeunes Filles in Porto-Novo. After grading the students’ oral and written productions, the study discovers that 75% of the student club members obtained the average grade of 10 out of 20, while only 12.5% of non-member students made it. It appears that students’ participation in English club activities is beneficial not only for improving their English language skills, but also for developing their personality. As for the EFL teachers, they report to have gained more in terms of innovative teaching strategies, and improvement their speaking skill, by attending the club.
Keywords: English club; speaking; writing; communicative EFL learning; Lycée Toffa 1er